A case of spontaneous heterotopic pregnancy in natural conception complicated with hemoperitoneum. Issue 2 (February 2020) - Aziz, Muhammad; Arronte, Julio
Abstract: Heterotopic pregnancy, defined as simultaneous intrauterine and ectopic gestations, is an uncommon occurrence in women who conceive without assisted reproduction techniques. We present the case of 28 years old female with strong family history of multiple gestations, who presented with acute severe abdominal pain and diagnosed with spontaneous heterotopic pregnancy in natural conception. Ectopic pregnancy was successfully removed surgically to conserve the uterine pregnancy. After one week, patient presented with vaginal bleeding and diagnosed with missed abortion and lost her desired uterine pregnancy. This case report discusses the significance of early diagnosis and treatment of heterotopic pregnancy to avoid both fetal and maternal morbidity and mortality. Practitioners should carry a high index of suspicion for heterotopic pregnancy in patients presenting with common symptoms and carry a family history of multiple gestation pregnancies. Abstract : Medicine; Reproductive medicine; Obstetrics and Gynecology; Reproductive System; Diagnostics; multiple pregnancy; fetomaternal mortality; pregnancy complications; reproductive history